2023
DOI: 10.3389/fgene.2023.1272446
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of microRNA in the regulation of biotic and abiotic stress in agronomic plants

Ramkumar Samynathan,
Baskar Venkidasamy,
Ashokraj Shanmugam
et al.

Abstract: The increasing demand for food is the result of an increasing population. It is crucial to enhance crop yield for sustainable production. Recently, microRNAs (miRNAs) have gained importance because of their involvement in crop productivity by regulating gene transcription in numerous biological processes, such as growth, development and abiotic and biotic stresses. miRNAs are small, non-coding RNA involved in numerous other biological functions in a plant that range from genomic integrity, metabolism, growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 165 publications
0
2
0
Order By: Relevance
“…MicroRNAs have become a research hotspot because they regulate gene transcription and thus affect plant productivity in many processes such as growth, development, and environmental stresses [85]. MiRNAs adaptive responses can increase plant survival in environments such as drought, salinity, and pathogens [86]. We found that 35 Jr4CLs and 30 Jm4CLs were predicted to be the target genes of 260 and 218 Arabidopsis miRNAs, respectively (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…MicroRNAs have become a research hotspot because they regulate gene transcription and thus affect plant productivity in many processes such as growth, development, and environmental stresses [85]. MiRNAs adaptive responses can increase plant survival in environments such as drought, salinity, and pathogens [86]. We found that 35 Jr4CLs and 30 Jm4CLs were predicted to be the target genes of 260 and 218 Arabidopsis miRNAs, respectively (Fig.…”
Section: Discussionmentioning
confidence: 88%
“… 1 As a matter of fact, plant miRNAs have been widely associated with several biological functions, including development and reproduction, 2 cell reprogramming, 3 secondary metabolism, 4 and biotic and abiotic stress responses. 5 …”
Section: Introductionmentioning
confidence: 99%